Efektifitas Pembelajaran PPKn dengan Pendekatan Saintifik pada SMP Negeri 40 Makassar - Musdalifah Syahrir (Universitas of Muhammadiyah Makassar, 2018)
The study aims at obtaining the description of the effectiveness of PPKn learning using scientific approach at SMPN 40 Makassar viewed from its implementation including (1) observing, (2) questioning, (3) experimenting, (4) associating, and (5) communicating. This study is descriptive qualitative research that describes the result of the study by describing the actual data obtained from the effectiveness of PPKn learning using scientific approach at SMPN 40 Makassar. The data source is selected by employing purposive sampling technique. Data is collected through interview, observation, and documentation. Data is analyzed using descriptive qualitative analysis by conducting data reduction, data presentation, conclusion or verification. The results of the study of the effectiveness of PPKn learning using scientific approach at SMPN 40 Makassar indicate that (1) the scientific approach in PPKn learning at SMPN 40 Makassar at the stage of observing, questioning, experimenting, associating, and communicating had been conducted effectively, (2) the scientific approach is yet to make the PPKn learning effective at SMPN 40 Makassar, proved by the implementation of learning activity using scientific approach that there are constraints face by the teacher and students, the students are not active yet in following the learning process, and it has yet to achieve PPKn learning objective using scientific approach.Keywords : Effectiveness of learning, scientific approach.